Increased survival of patients aged 0‐29 years with osteosarcoma: A period analysis, 1984‐2013. (10th July 2018) - Wu, Jinna; Sun, Huanhuan; Li, Jie; Guo, Yuanqing; Zhang, Kuibo; Lang, Chuandong; Zou, Changye; Ma, Haiqing
Abstract: Purpose: Osteosarcoma is the most common primary malignancy of bone, and typically occurs among children and adolescence. This study aims to evaluate treatment outcomes among children, adolescents and young adults with osteosarcoma over the three decades by the changes in the long‐term relative survival. Methods: Osteosarcoma incidence and relative survival data from Surveillance, Epidemiology, and End Results (SEER) registries during 1984‐2013 were analyzed. The survival differences over three decades, age, sex, race, and socioeconomic status (SES) were assessed by comparing Kaplan‐Meier curves. Results: The overall incidence of osteosarcoma kept relatively stable with 0.4 per 100 000 in the three decades with the peak incidence occurring in the aged 10‐19 group. The 10‐year relative survival rate (RSR) increased from 57.7% to 61.0% in the three decades, with the greatest increase in the aged 0‐9 group from 48.2% to 65.7%. The 10‐year RSR improved from 54.1% to 61.5% in males, and from 62.4% to 63.0% in females, respectively, in the three decades. Furthermore, survival dramatically improved from 30% to 60% in the high‐poverty group over the three decades. Conclusion: This study demonstrated that the overall incidence of osteosarcoma remained stable, with an improvement in survival in the three decades. The improved survival was greater in males than in females in the three decades. Furthermore, the survival significantly increased in high‐poverty group, which was attributed to increasing improved health care system and patients with low finance can also have access to receiving effective and consistent treatment without distinction. Abstract : The 10‐year relative survival improved in all age groups, especially for the aged 0‐9 group with the greatest increase from 48.2% to 65.7% in the three decades. Additionally, the improved survival was greater in males than in females, and the survival gap between sexes were narrowing over time in the three decades. Furthermore, there was a significant progressive relative survival increase from 30% to 60% in high‐poverty patients, with the survival gap between low‐poverty and high‐poverty groups significantly narrowing over time in the three decades.